2010
DOI: 10.1590/s0100-29452010005000106
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade sensorial dos frutos do abacaxizeiro 'imperial' cultivado em deficiência de macronutrientes e de boro

Abstract: A comercialização do abacaxi vem expandindo-se no mercado mundial principalmente por suas apreciáveis características de sabor, aroma e cor. A nutrição mineral da planta exerce uma influência acentuada na composição química do abacaxi. A inexistência de informações sobre a influência da deficiência nutricional na qualidade dos frutos do abacaxizeiro 'Imperial' motivou a realização de um experimento em casa de vegetação da Universidade Estadual do Norte Fluminense, em Campos dos Goytacazes-RJ, no período de 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…Close results were verified by Martins et al (2012), when they observed firmness of 7.99 kgf in 'Pérola' pineapple grown in a conventional production system. However, Ramos et al (2010), achieved a mean of 6.06 kgf in 'Imperial' pineapple, induced at eight months of age. In 'Vitória' pineapple, the value found for firmness was 8,195 kgf in fruits harvested under commercial Rev.…”
Section: Resultsmentioning
confidence: 98%
“…Close results were verified by Martins et al (2012), when they observed firmness of 7.99 kgf in 'Pérola' pineapple grown in a conventional production system. However, Ramos et al (2010), achieved a mean of 6.06 kgf in 'Imperial' pineapple, induced at eight months of age. In 'Vitória' pineapple, the value found for firmness was 8,195 kgf in fruits harvested under commercial Rev.…”
Section: Resultsmentioning
confidence: 98%
“…Nitrogen (N) is part of amino acids, amides, proteins, nucleic acid and coenzymes (Ramos et al, 2010). Potassium plays a role in plant metabolism, acting as an activator of several enzymes during photosynthesis, respiration, the opening of stomata and maintenance of cellular turgidity (Marschner, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the inadequate supply of a particular nutrient usually results in nutritional disorders. Ramos et al (2010) showed that N deficiency in cv. Imperial resulted in infructescences with high acidity, without aroma and flavor.…”
Section: Introductionmentioning
confidence: 99%
“…Of all the tropical fruits, pineapple is considered one of the most important, and its commercialization has been growing in the world market, mainly for its characteristics of flavor, aroma and color, appreciated in several regions (RAMOS, 2010).…”
Section: Introductionmentioning
confidence: 99%